Techniques for Defending from Buffer Overflow Vulnerability Security Exploits - Padmanabhuni, Bindu; Tan, Hee Beng Kuan (IEEE internet computing, 2019)
Recent reports reveal that majority of security violations are caused by weaknesses in code. Buffer overflow vulnerability is the most severe of security violations. Though wide range of solutions from static analysis techniques to hardware modifications were proposed to tackle the vulnerability they either fail to address the large scope of the problem or have limitations preventing their use and adoption. In this article, we discuss well-known buffer overflow vulnerability exploit mechanisms followed by comprehensive study of proposals for defending from such exploits along with review of tools used for supporting the process.